Age-Related Differences in Auditory Processing as Assessed by Amplitude-Modulation Following Responses in Quiet and in Noise - Parthasarathy, Aravindakshan; Cunningham, Paul A.; Bartlett, Edward L. (Frontiers in Aging Neuroscience, 2010)
Our knowledge of age related changes in auditory processing in the central auditory system is limited, unlike the changes in the peripheral hearing organs which are more extensively studied. This study aims to further understanding of temporal processing in aging using non-invasive electrophysiological measurements in a rat model system. Amplitude modulation following responses (AMFRs) were assessed using sinusoidally amplitude modulated (SAM) tones presented to aged (92-95 weeks old) and young (9-12 weeks old) Fischer-344 rats. The modulation frequency and sound level were systematically varied, and the SAM stimuli were also presented simultaneously with wide-band background noise at various levels. The overall shapes and cutoff frequencies of the AMFR temporal modulation transfer functions (tMTFs) were similar between young and aged animals. The fast Fourier transform (FFT) amplitudes of the aged animals were similar to the young in the 181Hz-512Hz modulation frequency range, but were significantly lower at most modulation frequencies above and below. There were no significant age related differences in the nature of growth or FFT amplitudes with change in sound level at 256Hz and 1024Hz modulation frequencies. The AMFR amplitudes were also not correlated with the ABR wave I or wave III amplitudes elicited for broadband click stimuli presented at the same sound level suggesting that sustained AMFR responses provide complementary information to phasic ABR responses. The FFT amplitudes varied significantly between young and aged animals for SAM stimuli in the presence of background noise, depending on the modulation frequency used and signal to noise ratio. The results show that the representation of temporally modulated stimuli is similar between young and aged animals in quiet listening conditions, but diverges substantially with the addition of background noise. This is consistent with a decrease in inhibition causing altered temporal processing with age.